Bioactive compounds of Boesenbergia sp. and their anti-inflammatory mechanism: A review - Aziiz Mardanarian Rosdianto, Irma Melyani Puspitasari, Ronny Lesmana, Jutti Levita (Journal of Applied Pharmaceutical Science, 2020)
Boesenbergia sp. (Zingiberaceae) has been empirically used in Indonesia, to treat rheumatism. The rhizome of Boesenbergia rotunda contains essential oils (nerol, camphor, cineole, fenchene, hemanthidine, and limonene), flavonoids (alpinetin, boesenbergin, cardamonin, pinostrobin, pinocembrin, geraniol, panduratin, and silybin), and polyphenols (caffeic acid, coumaric acid, chlorogenic acid, hesperidin, kaempferol, naringin, and quercetin), which explain its many interesting pharmacological activities (antifungal, anti-inflammatory, antimicrobial, antibacterial, anticancer, antimutagenic, antiparasitic, antiulcer, antileukemia, hepatoprotective, and antiviral). This review focuses on the bioactive compounds in Boesenbergia sp. and their molecular mechanism in reducing inflammation. Of all bioactive compounds, panduratin A and 4-hydroxypanduratin A have proven their activity in inhibiting the production of nitric oxide and PGE2 as well as on tumor necrosis factor-alpha. Moreover, this paper also provides other uses of this plant species as well as future study aspects.
Keywords: B. rotunda, flavonoid, kaempferol, panduratin A, quercetin, Zingiberaceae.